Intensity of menopausal symptoms and quality of life in climacteric women - Szadowska-Szlachetka, Zdzisława C. (Prz Menopauzalny, 2020)
Menopause is a difficult period in a woman’s life, associated not only with the end of menstruation, but also with symptoms such as hot flashes, sweating, dizziness, and palpitations which occur due to fluctuations in the hormones oestrogen and progesterone. The aim of this study was to evaluate the quality of life of women (aged 48-55 years) in the physical, mental and social spheres, to determine the intensity of menopause symptoms and to ascertain whether the above indicators are influenced by sociodemographic factors. The study was conducted by diagnostic survey using two tools – the WHOQOL-BREF questionnaire for the measurement of the quality of life and the Kupperman index, which measures the severity of menopause symptoms. A total of 161 women not using hormone replacement therapy were examined. In their case, the intensity of menopause symptoms was moderate. The respondents assessed their functioning in the social sphere with the highest number of points (3.65) and in the physical sphere with the lowest number of points (3.14). The intensity of menopause symptoms positively correlated with the evaluation of the quality of life by the respondents. Higher assessment of the quality of life was reported by women working in a given period of time, with good material status, sexually active. The respondents suffered from chronic diseases, most often arterial hypertension. The occurrence of chronic diseases – arterial hypertension, coronary artery disease, diabetes and osteoporosis – negatively affected the quality of life of the respondents.